Evaluation of processed rubber seed oil Hevea brasiliensis utilization as lipid source in Clarias gariepinus feed - Annisa, Nuraini; Suprayudi, Muhammad Agus; Setiawati, Mia; Fauzi, Ichsan Ahmad (Indonesian Society of Scientific Aquaculture (ISSA), 2020)
ABSTRACT Clarias gariepinus rearing is mostly done with intensive systems that use a lot of commercial feed. The price of raw material for the feed lipid source which is currently the main source of fatty acids in freshwater fish feed continues to increase and compete with human needs. Rubber seed oil (RSO) is considered feasible to be an alternative. This study aimed to evaluate the use of heated RSO as alternative lipid source in C gariepinus feed. The results of this study indicated that heating could reduce HCN levels in RSO by 95%. Even after heated RSO was inserted into the feed formulation there is still HCN in feed, however it did not affect the survival rate of C. gariepinus statistically. Heated RSO based feed shows a specific growth rate that was higher than non-heating RSO-based feed. Feeding with heated RSO also did not affect nutrient retention in C. gariepinus. This also followed by blood profile, blood chemistry and body fatty acids profile, MDA levels and SOD levels which were almost same as treatment feed using fish oil and corn oil. From these results, it can be concluded that heating can reduce 95% HCN content in RSO and can be used as a lipid source in C. gariepinus feed. Keywords: Aquaculture, essential fatty acids, growth performance, HCN, rubber seed oil. ABSTRAK Budidaya ikan lele Clarias gariepinus dengan sistem intensif menggunakan banyak pakan buatan. Harga bahan baku untuk sumber lemak pakan terus meningkat dan bersaing dengan kebutuhan manusia. Minyak biji karet (MBK) layak menjadi alternatif. Penelitian ini bertujuan mengevaluasi penggunaan MBK yang dipanaskan sebagai sumber lemak alternatif dalam pakan ikan lele. Hasil penelitian menunjukkan proses pemanasan dapat mengurangi kadar HCN pada MBK hingga 95%. Walaupun masih terdapat sejumlah kecil HCN pada pakan berbasis MBK yang dipanaskan, tetapi tidak memengaruhi tingkat kelangsungan hidup ikan lele (p>0,05). Pakan berbasis MBK proses pemanasan menunjukkan laju pertumbuhan spesifik yang lebih tinggi dari pakan berbasis MBK yang tidak dipanaskan. Pemberian pakan berbasis MBK proses pemanasan juga tidak memengaruhi retensi nutrisi ikan lele. Demikian pula parameter profil darah, kimia darah, profil asam lemak tubuh, kadar MDA dan kadar SOD hampir sama dengan pakan perlakuan berbasis minyak ikan dan minyak jagung. Sehingga dapat disimpulkan MBK proses pemanasan dapat mengurangi 95% kandungan HCN dan dapat digunakan sebagai sumber lemak dalam pakan ikan lele. Kata kunci: Akuakultur, asam lemak esensial, HCN, kinerja pertumbuhan, minyak biji karet.